2015
DOI: 10.1111/jnc.13123
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking glutamate carboxypeptidase II develop normally, but are less susceptible to traumatic brain injury

Abstract: Glutamate carboxypeptidase II (GCPII) is a transmembrane zinc metallopeptidase found mainly in the nervous system, prostate and small intestine. In the nervous system, glia-bound GCPII mediates the hydrolysis of the neurotransmitter N-acetylaspartylglutamate (NAAG) into glutamate and N-acetylaspartate. Inhibition of GCPII has been shown to attenuate excitotoxicity associated with enhanced glutamate transmission under pathological conditions. However, different strains of mice lacking the GCPII gene are reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 66 publications
3
66
1
Order By: Relevance
“…Such a difference was not found between our wild type and Abcc5 Ϫ/Ϫ mice, however (data not shown). Dedicated behavior assays should be performed to find more subtle neurological phenotypes, such as the reduced social interaction found in GCP2 ϩ/Ϫ mice (72) and the reduced susceptibility to traumatic brain injury found in GCP2 Ϫ/Ϫ mice (73). Behavioral phenotypes would likely be more obvious in humans, but ABCC5-deficient humans have never been described, despite the likely existence of null alleles (74).…”
Section: Discussionmentioning
confidence: 99%
“…Such a difference was not found between our wild type and Abcc5 Ϫ/Ϫ mice, however (data not shown). Dedicated behavior assays should be performed to find more subtle neurological phenotypes, such as the reduced social interaction found in GCP2 ϩ/Ϫ mice (72) and the reduced susceptibility to traumatic brain injury found in GCP2 Ϫ/Ϫ mice (73). Behavioral phenotypes would likely be more obvious in humans, but ABCC5-deficient humans have never been described, despite the likely existence of null alleles (74).…”
Section: Discussionmentioning
confidence: 99%
“…In the brush border of the small intestine the same enzyme also exerts folyl-poly-g-Glu carboxypeptidase activity, which is thought to mediate dietary folate uptake (Pinto et al, 1996;Navrátil et al, 2014). The in vivo requirement of these biochemical activities could not be clearly demonstrated since knock-out mice of GCPII show normal development and behavior, most likely because of functional redundancy with the close paralog GCPIII (Bacich et al, 2002;Gao et al, 2015). GCPII is also expressed at lower levels in various other tissues and is strongly up-regulated in prostate cancer cells and the neo-vasculature of most solid tumors.…”
mentioning
confidence: 99%
“…This non-invasive approach is complementary to our earlier microdialysis and histological studies [3, 8, 9]. The purpose of this study was to obtain further evidence of the usefulness of GCP-II inhibition as a clinical approach to treating TBI.…”
Section: Introductionmentioning
confidence: 92%
“…NAAG peptidase inhibitors inhibit the GCP-II enzyme and can reduce the concentration of Glu via two main routes: increasing the duration of NAAG activity at mGluR3, and reducing the degradation of NAAG into NAA and Glu, leading to decreased cell death in models of TBI [2]. It has been reported that GCP-II-knockout (KO) mice develop normally, but demonstrate less astrocyte damage and neurodegeneration after TBI [3]. Together, these findings imply that inhibiting GCP-II is a good approach for reducing the secondary neurodegeneration induced by Glu after TBI, but further experimental evidence is required.…”
Section: Introductionmentioning
confidence: 99%